Proceedings of the Thirteenth Conference on Computational Natural Language Learning - CoNLL '09 2009
DOI: 10.3115/1596374.1596381
|View full text |Cite
|
Sign up to set email alerts
|

A metalearning approach to processing the scope of negation

Abstract: Finding negation signals and their scope in text is an important subtask in information extraction. In this paper we present a machine learning system that finds the scope of negation in biomedical texts. The system combines several classifiers and works in two phases. To investigate the robustness of the approach, the system is tested on the three subcorpora of the BioScope corpus representing different text types. It achieves the best results to date for this task, with an error reduction of 32.07% compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
143
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(146 citation statements)
references
References 15 publications
(7 reference statements)
2
143
1
Order By: Relevance
“…Agarwal and Yu [39] developed the NegScope algorithm that utilizes conditional random fields to detect negations, but it had a lower performance in comparison to NegEx. Fujikawa et al [40] developed the NegFinder algorithm for determining the scope of negation cues by adding syntactic information to the algorithm of Morante et al [36,38] that utilizes k-nearest neighbor classification as discussed above. This algorithm should not be mistaken for the NegFinder algorithm by Mutalik et al [25].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Agarwal and Yu [39] developed the NegScope algorithm that utilizes conditional random fields to detect negations, but it had a lower performance in comparison to NegEx. Fujikawa et al [40] developed the NegFinder algorithm for determining the scope of negation cues by adding syntactic information to the algorithm of Morante et al [36,38] that utilizes k-nearest neighbor classification as discussed above. This algorithm should not be mistaken for the NegFinder algorithm by Mutalik et al [25].…”
Section: Related Workmentioning
confidence: 99%
“…Rokach et al [37] designed an algorithm for learning regular expressions using the longest common subsequence algorithm followed by decision tree classification. Morante and Daelemans [38] proposed a machine learning algorithm utilizing k-nearest neighbor classification in addition to Support Vector Machines (SVMs) and conditional random fields to determine the scope of negation. Uzuner et al [24] proposed the StAC statistical assertion classification algorithm and showed that it outperforms the rule-based ENegEx algorithm.…”
Section: Related Workmentioning
confidence: 99%
“…It is important to note that the main source of error here is the NegatedPredicate-to-BioScopeScopeSpan trans- Table 3: PCS measures from previous BioScope span detection approaches and our end-to-end system. Col. 1-3: end-to-end systems (Morante and Daelemans, 2009), (Ballesteros et al, 2012), and (Velldal et al, 2012);…”
Section: Our Negatedpredicate Predictormentioning
confidence: 99%
“…In particular, we adopt the practice of solving scope resolution as a sequence labeling task (Morante and Daelemans, 2009;Lapponi et al, 2012;White, 2012) based on syntactic features Lapponi et al, 2012;Packard et al, 2014). In contrast to many of the previous systems that have used constituency-based representations Packard et al, 2014), we base our syntactic features on dependency representations, similar to the approach of Lapponi et al (2012).…”
Section: Introductionmentioning
confidence: 99%
“…While many research-based systems have been developed, with the aim of exploring features and algorithms to advance the state-of-the-art in terms of performance (Morante and Daelemans, 2009;Lapponi et al, 2012;Packard et al, 2014;Fancellu et al, 2016), many of them are difficult to employ in practice, due to layered architectures and many dependencies, and furthermore, most are simply not made publicly available in the first place.…”
Section: Introductionmentioning
confidence: 99%